Heterogeneous identities in a homogeneous place. Sound analysis of mercato delle erbe - Barbato, Giuseppe; Colonnelli, Edoardo; Marchegiani, Noemi (E|C, 2020)
Semiotic studies show how sensory perception has a role into the building of a meaningful experience. Is this true also for sound? If so, what relationships has sound with other sensory experiences? The best way to answer to these questions is researching in the field: we chose Bologna’s Mercato delle Erbe and we conducted, through a semiotic perspective, an ethnographic analysis, observing and listening directly to the place. The corpus has been divided into several sections, which have been observed and listened to for an extended period, in different hours of the day. The data gained in this way were analysed starting from the general characteristics of sound: this allowed us to identify the significant site outlines, the social practices developed there at different hours and by different types of users. The final result is that sounds have a strong significant potential, allowing us to identify specific paths and activities of a place and, finally, contributing to the potentiality of multi-sensory experience.